China-Pakistan strategic cooperation in the post September 11 period - Jamil, Sobia
China has remained most significant strategic partner of Pakistan and its relations have mainly been driven by its national interests and strategic goals to maintain balance of power in South Asia. The nuclearisation of India in the region and its strategic partnership with US and its growing presence in Asia Pacific has strengthened strategic partnership between China and Pakistan. China and Pakistan relationship is based upon mutual interests at bilateral, regional and global levels. At the bilateral level, China considers Pakistan as a feasible energy and trade corridor. For Pakistan, China's strategic cooperation is a constant source of security against India. In the defense sector, Pakistan has become the biggest importer of Chinese defense equipment. Pakistan's Army, Navy, and Air Forces are equipped with Chinese made defense technology. China-Pakistan Economic Corridor (CPEC); a flagship project of OBOR has enhanced economic cooperation between China and Pakistan. This research attempts to analyze regional and global developments in the post 9/11 period that have impacted China-Pakistan strategic relations in the changing geopolitical scenario. It further examines the economic and security dimensions of strategic partnership between Pakistan and China and also explored the level that both countries have enhanced cooperation in the changing strategic scenario of the post 9/11 period. Finally, the research assesses the benefits that Pakistan and China are getting through their strategic cooperation. The study is empirical in nature conducted by using descriptive and analytical method of qualitative research and case study design. Data were collected through existing literatures, published research works and interviews with experts on China-Pakistan relations to formulate an approach for establishing the link between emerging security scenario of South Asia and PakistanChina strategic cooperation in the post 9111 period. The findings of this research are that in the post 9111 scenario, the Indo-United States strategic partnership makes India an assertive power in the region which poses serious threats to existing balance of power in South Asia. On one hand, growing mistrust between the United States and Pakistan is one of the major reasons which lead Pakistan to push itself more towards China for its defense and economic needs. On the other hand, China has its own regional and global objectives to achieve. Due to these mutual interests, Qh· It: and Pakistan have developed an interdependent partnership which is mutually eneft&ial for both the states. The research recommended that Pakistan and China sh<0'uld furilher consolidate their strategic partnership not only for regional peace and stabii ity but also for the socio economic development of the people of both the states and he region at large.